Virtual and Augmented Reality for Neurofunctional Recovery and Human Movement Analysis - Brandão, Alexandre F.; Guimarães, Marcelo P.; Dias, Diego R. C.; Brega, José R. F. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais Estendidos do XXIV Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2022.226937, 2022)
We present the research results on virtual reality and neurofunctional recovery, part of a multidisciplinary and inter-institutional project. The BRAINN_VR Initiative is a line of research and technological development in virtual rehabilitation solutions running on the Brazilian Institute for Neuroscience and Neurotechnology – BRAINN.